Connecting to Clients and Employees - Wunda, Adrianus (International Research Journal of Management, IT & Social Sciences, 2015)
Performance issues for companies is a very important issue. In the absence of good performance unlikely companies could produce a competitive product. Performance improvements have positive implications for the company itself, meaning that the company can produce the quantity and quality of the product that is optimal with competitive price. It also has enormous implications, positive to the quality of life of employees, due to contribute to the improvement of the quality of life of employees. Employee performance will be increased if supported by the application of a system of performance management and career development system is good and effective as well as application of teamwork and participation of employees.